Sistem Informasi Prioritas Pada Layanan Publik SPBE Kota Palangkaraya - Hilarion Hamjen (Jurnal Studi Komunikasi dan Media, 2023)
Public Services are essential in government,especially with the implementation of SPBE, where public services can become more efficient and effective with the support of a good information system.However, the availability of information systems also needs to be prioritized according to the competence of ICT human resources, so the research aims to identify and map the priority information systems in SPBE public services in Palangkaraya City government.This research was conducted using quantitative approach through a survey of all 33 OPD/respondents and saturated sample.In addition, this research was also supported by qualitative approach.The data was mapped using the impact ease implementation matrix and analyzed descrively.Based on the Results, there are 24 information system or applications categorized easy to access and have high impact (high easy..Meanwhile, the information systems or applications categorized as difficult to access but have high impact (high-hard) Amounted to 10 applications.By identifying and mapping these priority information systems, it is hoped that their development and utilization can minimize errors caused by human in SPBE public services. Keywords: Public Services, Information System, Prioritization, Applications, SPBE